3D printing of chemical-empowered tendon stem/progenitor cells for functional tissue repair. (April 2021) - Zhang, Yanjie; Lei, Tingyun; Tang, Chenqi; Chen, Yangwu; Liao, Youguo; Ju, Wei; Zhang, Hong; Zhou, Bo; Liang, Renjie; Zhang, Tao; Fan, Chunmei; Chen, Xiaoyi; et al.
Abstract: Tendon injuries are the leading cause of chronic debilitation to patients. Tendon stem/progenitor cells (TSPCs) are potential seed cells for tendon tissue engineering and regeneration, but TSPCs are prone to lose their distinct phenotype in vitro and specific differentiation into the tenocyte lineage is challenging. Utilizing small molecules in an ex vivo culture system may be a promising solution and can significantly improve the therapeutic applications of these cells. Here, by using an image-based, high-throughput screening platform on small molecule libraries, this study established an effective stepwise culture strategy for TSPCs application. The study formulated a cocktail of small molecules which effected proliferation, tenogenesis initiation and maturation phases, and significantly upregulated expression of various tendon-related genes and proteins in TSPCs, which were demonstrated by high-throughput PCR, ScxGFP reporter assay and immunocytochemistry. Furthermore, by combining small molecule-based culture system with 3D printing technology, we embedded living, chemical-empowered TSPCs within a biocompatible hydrogel to engineer tendon grafts, and verified their enhanced ability in promoting functional tendon repair and regeneration both in vivo and in situ . The stepwise culture system for TSPCs and construction of engineered tendon grafts can not only serve as a platform for further studies of underlying molecular mechanisms of tenogenic differentiation, but also provide a new strategy for tissue engineering and development of novel therapeutics for clinical applications.